Audit of the risk management system in order to increase its effectiveness - D. V. Shamin (Real Economics Publishing House, 2017)
The article is devoted to the problems increasing the effectiveness of the risk management system (RMS) within the framework the implementation of mega-projects in the industry. The application modern tools of risk management in the new business environment, the urgency of the RMS audit disclosed steps and audit procedures.